2016
DOI: 10.1037/bul0000058
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic review of the association between perceived social support and depression in childhood and adolescence.

Abstract: This meta-analysis evaluated the relation between social support and depression in youth and compared the cumulative evidence for 2 theories that have been proposed to explain this association: the general benefits (GB; also known as main effects) and stress-buffering (SB) models. The study included 341 articles (19% unpublished) gathered through a search in PsycINFO, PsycARTICLES, ERIC, and ProQuest, and a hand search of 11 relevant journals. Using a random effects model, the overall effect size based on k = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

70
448
4
17

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 599 publications
(588 citation statements)
references
References 415 publications
70
448
4
17
Order By: Relevance
“…Our phenotypic results follow a similar pattern to previous studies which have found stronger links between the quality (in contrast to quantity) of support and mental health outcomes in both adults 24,42,43,51 and children 16,17 . We add additional weight to the evidence by finding that genetic correlations are also higher between support quality and mental health in late adolescence.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our phenotypic results follow a similar pattern to previous studies which have found stronger links between the quality (in contrast to quantity) of support and mental health outcomes in both adults 24,42,43,51 and children 16,17 . We add additional weight to the evidence by finding that genetic correlations are also higher between support quality and mental health in late adolescence.…”
Section: Discussionsupporting
confidence: 91%
“…One meta-analysis found that the association between support and mental health became stronger with increasing age from early childhood into late adolescence 16 though this moderation effect was not replicated in a later meta-analysis 17 . Looking across a broad age range from early childhood to 20 years, both meta-analyses found perceived quality of support to be more strongly associated with mental health outcomes (better wellbeing and fewer depressive symptoms) than quantity of support.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Overall, these findings are consistent with interpersonal models of depression which suggest that interpersonal impairment, such as lack of social support and conflict with parents, plays a unique role in the development of depression (Rueger, et al, 2016; Haggerty & Williams, 1999). Consistent with previous findings (e.g., Eddy et al, 2015) the longitudinal association between academic impairment and depression was signifciant in the regression model.…”
Section: Discussionsupporting
confidence: 82%
“…Fourth, professionals working with adolescents who use the Internet excessively may screen for depressive symptoms and include support for improving social skills through group counselling sessions which provide face‐to‐face interactions with others (Chrismore, Betzelberger, Bier, & Camacho, ) and healthy coping strategies such as physical exercise to manage depressed mood (Carter, Morres, Meade, & Callaghan, ). Prevention efforts can focus on the improvement of parenting skills, family support, and family cohesion to offer protection against depressive symptoms in youth, which in turn are likely to contribute to healthy use of the Internet (Rueger, Malecki, Pyun, Aycock, & Coyle, ; Yu et al ., ). Lastly, given that heavy Internet users were more likely to report drinking alcohol, professionals should pay particular attention to helping youth who are heavy Internet users understand the ways in which online social interactions and online alcohol marketing exposure may lead to the adoption of risky values and behaviours and can pave the way towards a higher likelihood of early alcohol use.…”
Section: Discussionmentioning
confidence: 99%